Vertebral Artery Dissections: A Retrospective Data Analysis of a Single Center - Yakupoğlu, Abdullah; Korkmazer, Bora; Arslan, Serdar; Üstündağ, Ahmet; Kızılkılıç, Osman; Koçer, Naci; Işlak, Civan (Cerrahpaşa Medical Journal, 2022)
Objective: The aim of our study is to reveal the etiological, anatomical, and morphological characteristics and treatment results of vertebral artery dissections. Methods: A total of 97 patients, who underwent at least 1 digital subtraction angiography examination and had proven to have vertebral artery dissection in the interventional neuroradiology department between 1994 and 2019, were included in this study. Statistical analyses were performed to evaluate the age, gender, onset of symptom presentation, history of any trauma in the head and neck region, medical history of known diseases or additional vascular pathologies, follow-up duration, and morphological characteristics of the dissected vertebral arteries. Results: Of 97 patients, 53 (54.6%) were male and 44 (45.4%) were female. The mean patient age was 44.5 ± 14.2 years (range: 3-75). Thirty-seven (38.1%) patients had chronic and 60 (61.9%) patients had acute vertebral artery dissection. While dissection was detected in the bilateral vertebral artery in 13 (13.4%) patients, involvement of multiple segments was noted in 12 (12.4%) patients. The rate of fusiform/aneurysmal dilatation was significantly increased in vertebral artery dissection on the dominant or codominant side, and a greater rate of luminal irreg ulari ty/st eno-o cclus ion was evident on the dissection of nondominant vertebral artery (P < .001). Conclusion: Patients with vertebral artery dissection may present with a wide spectrum of signs, ranging from asymptomatic to severe strokes of vertebrobasilar system or subarachnoid hemorrhage. As a result of advances in imaging modalities, endovascular techniques, and materials, especially in the last 2 decades, significant progress has been made in the treatment of vertebral artery dissections and related pseudoaneurysms. Cite this article as: Yakupoğlu A, Korkmazer B, Arslan S, et al. Vertebral artery dissections: A retrospective data analysis of a single center. Cerrahpaşa Med J. October 10, 2022. 46(3):183-188.